Caste, wealth and geographic equity in program reach and expected outcomes: an exploratory analyses of Suaahara in Nepal - Cunningham, Kenda; Adhikari, Ramesh P.; Gupta, Poonam; Suresh, Shalini; Chen, Jiaxin; Sen, Aman; Shrestha, Manisha Laxmi; Garn, Kristine; Rana, Pooja Pandey; Adhikari, Debendra (Frontiers in Nutrition, 2024)
IntroductionMonitoring and evaluation of maternal and child nutrition programs typically concentrates on overall population-level results. There is limited understanding, however, of how intervention reach and expected outcomes differ among sub-populations, necessary insight for addressing inequalities. These analyses aim to determine if maternal exposure to social and behavior change (SBC) interventions is associated with scales of maternal practices (antenatal care, iron and folic acid in pregnancy, diet in pregnancy, postnatal care, iron and folic acid postpartum, and maternal dietary diversity) and child practices (institutional birth, health mothers’ group participation, growth monitoring and promotion, early initiation of breastfeeding and infant and young child feeding) in Nepal, overall and by wealth, caste, and geography.MethodsCross-sectional data from 2022 from the USAID-funded Suaahara program in Nepal were used for analysis. The study focused on households with children aged 0–2 years (N = 1815). Descriptive analysis was followed by regression models, adjusted for potentially confounding child, mother, and household factors, as well as community-level clustering.ResultsGreater intensity of maternal engagement with the SBC interventions was positively associated with both scales for maternal and child nutrition-related practices. The magnitude of the positive associations, however, was less for the socially excluded caste versus others for maternal nutrition; there was almost no caste-based variation in associations for child nutrition. Positive associations were found only among the lower 40% socio-economically when mothers engaged with at least two platforms for maternal nutrition and at least three platforms for child nutrition. In contrast, engagement with one platform for the relatively wealthier was positively associated with both maternal and child outcomes. Similarly, the positive associations were stronger among those residing in the terai (lowland plains) than those in the hills and mountains for both maternal and child outcomes.DiscussionThe scope for improving maternal and child nutrition practices is significant, in part via well-designed, targeted, SBC programs. These analyses highlight the importance of considering different domains of equity both in implementation and related research. Further mixed methods research is needed to more deeply explore why certain types of interventions reach and/or have a greater effect on sub-populations.